3(5x-3)-3(2x-5)=

Simple and best practice solution for 3(5x-3)-3(2x-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x-3)-3(2x-5)= equation:


Simplifying
3(5x + -3) + -3(2x + -5) = 0

Reorder the terms:
3(-3 + 5x) + -3(2x + -5) = 0
(-3 * 3 + 5x * 3) + -3(2x + -5) = 0
(-9 + 15x) + -3(2x + -5) = 0

Reorder the terms:
-9 + 15x + -3(-5 + 2x) = 0
-9 + 15x + (-5 * -3 + 2x * -3) = 0
-9 + 15x + (15 + -6x) = 0

Reorder the terms:
-9 + 15 + 15x + -6x = 0

Combine like terms: -9 + 15 = 6
6 + 15x + -6x = 0

Combine like terms: 15x + -6x = 9x
6 + 9x = 0

Solving
6 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 9x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 9x = 0 + -6
9x = 0 + -6

Combine like terms: 0 + -6 = -6
9x = -6

Divide each side by '9'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| A-(-3)=25 | | sin(40)=12/x | | y/-9=4 | | x^6-2x^3-4=0 | | 19m+23n+-3n= | | 2x-27=312 | | 7x-19+3x+9=180 | | -(5x-3)-3(2x-5)= | | (4x-6)/3=-2 | | 6*8*18= | | 0.49=cos(x) | | -7(3p+2)40=3(5p+6) | | 18*14*2= | | 5x+32=67 | | N/25-7=-82 | | 3x-2+7+3x-2+7=133 | | -9-5+2-8-9= | | 4x+6+x=180 | | 67y=45n+13 | | 2448/48=x | | X(x-8)=x^2+5x | | 0=40-(1.1xd) | | 49x^2-252x+224=0 | | 42-2x=125 | | 30-5=17+H | | 18(3d)+12d=4884 | | 72x^2=98 | | 3p=10-1 | | -9v-5v-v+7v+5v= | | 3n+8a=144 | | 4+x+8=-48 | | 30+15=2x+4 |

Equations solver categories